Vigabatrin induced Cell loss in the Cerebellar Cortex of Albino Rats - Deepa Singh (Journal of Clinical and Diagnostic Research, 2013)
Background: Vigabatrin is used as the drug of choice in resistant epilepsy and infantile spasms. Ataxia, tremors and abnormal gait have been frequently reported following the use of this drug, indicating an involvement of the cerebellum. Objectives: The present study was designed to study the histopathological effects of Vigabatrin on the cerebellum of albino rats. Material and Methods: Albino Rats were divided into an experimental and a control group. Vigabatrin was administered intra–peritoneally to the experimental group in graded doses for a period of 4 weeks. At the end of the treatment period, rats were sacrificed and brains were dissected out. The cerebellum was separated and fixed. Slides were prepared for histological examination. Results: Decreased cell counts in the cerebellar cortex secondary to toxic injury were found. Severity increased with increasing doses. Interpretation and conclusion: Vigabatrin may be neurotoxic and should be used with caution, assessing cerebellar function at regular intervals.